The use of mnemonics in foreign language teaching - Elena V. Revina (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article deals with searching of efficient way to memorize a lot of new information, that is necessary to modern society. Cultural and economic necessity to learn foreign languages quickly and efficiently is emphasized. The idea of suitable use of new memorization technique is based on. It makes it possible to remember a lot of new information. The author points out the intense motivation of learners. The author stresses involuntary memorizing which is based on expressive means of language and on emotional upheaval during studies. Searching of intensification methods and educational facilities is the purpose of this article. One way to deal successfully with this problem is using of specific mnemonic techniques. The author states that learning of teaching material depends on personal characteristics (memory type, temperament, intelligence, life experience). In this connection the author proposes some techniques to work with memory aids depended on memory aids according to memory type and type of thinking. The author used mnemonic techniques. The effectiveness of using these techniques was studied by the author. It is concluded that implementation of the used mnemonic techniques is efficient if different types of memory (auditory and visual, auditory, visual and motor) are combined. The problem of rational use of mnemonic techniques is presented in the program design for the use at the lessons of the German language.